ANTIBACTERIAL ACTIVITY OF COMBINED ETHANOL EXTRACTS OF CLITORIA TERNATEA FLOWERS AND JATROPHA GOSSYPIFOLIA LEAVES AGAINST ESCHERICHIA COLI - Sabariah Sabariah; Sabrina Intan Zoraya; Dinda Ayuni Rusma Putri (International Archives of Medical Sciences and Public Health, 2026)
The growing resistance of Escherichia coli to antibiotics has increased interest in plant-derived antibacterial agents. This study evaluated the antibacterial activity of combined ethanol extracts of Clitoria ternatea flowers and Jatropha gossypifolia leaves against E. coli. An in vitro experimental study with a post-test-only design was conducted. Extracts were prepared by maceration using 96% ethanol and subjected to phytochemical screening. Antibacterial activity was assessed using the disk diffusion method at concentrations of 20%, 40%, 60%, 80%, and 100%, with ciprofloxacin and dimethyl sulfoxide (DMSO) as controls. Each treatment was tested in four replicates. Phytochemical screening identified alkaloids, flavonoids, tannins, phenolic/hydroquinone compounds, and steroids. The largest inhibition zone was observed at 20% (12.25mm), followed by 40% (10.25 mm), 60% (8.00 mm), and 80% (6.25mm), while no inhibition occurred at 100%. Significant differences were found among groups (p < 0.001). These findings indicate measurable but limited antibacterial activity against E. coli.